Strategic Purchasing of Manpower: The Necessity of a Workforce Pool for a Construction Company - Pettersson, Maria; Petersson, Hanna (My University, 2017)
A case company in the construction industry, in this report referred to as Contractor Inc., is one of Sweden’s largest main contractors. Contractor Inc. is, like other construction companies in Sweden, lacking both blue-collar workers and white-collar workers. To deal with the demand for additional workers, Contractor Inc.’s current strategy is to purchase manpower from subcontractors and staffing agencies. However, there are disadvantages with external personnel. For example, Contractor Inc. does not have full control over that the external workers follow security routines and the company-specific code of conduct. Likewise, Contractor Inc. does not have control over the delivered quality of the work carried out by external workers, so there might be additional costs to redo some work. Also, the price for the external workforce can consist of additional costs that have not been calculated in the budget of projects. The issue regarding strategic purchasing of manpower at Contractor Inc. is investigated in this case study by conducting a literature review and interviews with internal employees at Contractor Inc. The findings show that the construction labour market is increasingly characterised of foreign workers from, for example, Eastern Europe. These blue-collar workers are often skilled in specialised areas within construction, and many of them are motivated to come to Sweden to work. Therefore, it is suggested to benefit from the available foreign workers, through an implementation of an internal workforce pool. The internal workforce pool is suggested to be an internal function at Contractor Inc., providing workers for all business units. The findings from this study show that an internal workforce pool can consist of both bluecollar workers and white-collar workers, specialised in certain construction areas. An internal workforce pool at Contractor Inc. would result in greater flexibility when planning manpower, increased control over that the workers follow the security routines and code of conduct, enlarged control over the delivered quality on the projects, and there would be no hidden costs regarding the price of the workers. The workforce pool is suggested to start as a pilot project with concrete workers, and the proposed location is Poland. If the pilot project is successful, it is suggested that other blue-collar workers and white-collar workers can be obtained from the pool. Thus, this study will review the advantages and challenges with the commissioning of an internal workforce pool for Contractor Inc.
Keywords: Transport; Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics